KUFRI MOHAN-A NEW HIGH YIELDING TABLE POTATO VARIETY - Kumar, Satish Luthra (Potato Journal, 2017)
ABSTRACT: Kufri Mohan is a medium maturing, main season, high yielding table purpose potato variety suitable for cultivation in Indo-Gangetic plains (northern and eastern). It is a clonal selection from a cross between MS/92-1090 x CP1704. Its plants are tall, semi-compact and vigorous with field resistance to late blight. It produces white cream, ovoid tubers with shallow eyes and white flesh. It possesses good keeping quality and moderate tuber dry matter (15-18%). It produces >90% marketable tuber yield and is capable of yielding 35-40 t/ha under optimum agronomical practices.Â